Postgraduate Colloquium - Sorooshian, Shahryar; M., Waris; Senthil Kumar , T.; Hasahudin, Hassan; Ida Rizyani, Tahir; Nor Sofea, Iman (FIM-UMP, 2016)
Postgraduate Colloquium was held on 18th February 2016.